Serotypes/groups distribution and antimicrobial resistance of invasive pneumococcal isolates: implications for vaccine strategies. - Kyaw, M. H. (Cambridge University Press, 2000)
Based on the invasive pneumococcal isolates referred to reference laboratories in Scotland in 1988-99, we identified the distribution of serotypes/groups and their antimicrobial resistance patterns in order to evaluate the coverage of polysaccharide and the new pneumococcal conjugate vaccines. A total of 5659 invasive isolates were included. Of these, 5124 (90.5%) were blood isolates, 308 (5.5%) were CSF isolates, 143 (2.5%) were blood and CSF and 84 (1.5%) were other normally sterile isolates. The most prevalent 11 serotypes/groups were 14, 9, 19, 6, 23, 1, 3, 4, 7, 8 and 18, in numerical order. These accounted for 84% of total serotypes/groups. The serotypes/groups included in the 23 and 14-valent polysaccharide vaccines accounted for 96% and 88% of all isolates. Both vaccines accounted for 98% of penicillin non-susceptible and 100% of erythromycin non-susceptible isolates. The 7, 9, and 11-valent conjugate vaccines covered 61, 68 and 80% of invasive isolates respectively. The coverage of these vaccines was substantially higher in youngest age group with 84, 86 and 93% of invasive isolates in children < 2 years included in the 7, 9 and 11-valent conjugate vaccines compared with 58, 64 and 77% in adults > or = 65 years of age. The serotype/group distribution of invasive isolates in Scotland varied from year to year over the period 1993-9. The coverage of the 23-valent vaccine remained above 95% in each year but the coverage of the 7, 9 and 11-valent conjugate vaccines showed more marked fluctuation with coverage as low as 53, 60 and 75% in some years. Continued surveillance of invasive pneumococcal isolates is required to inform the development of appropriate vaccine strategies to prevent pneumococcal disease in Scotland.